2022
DOI: 10.1186/s12903-022-02314-y
|View full text |Cite
|
Sign up to set email alerts
|

Parental psychosocial factors, unmet dental needs and preventive dental care in children and adolescents with special health care needs: A stress process model

Abstract: Background Children and adolescents with special health care needs (SHCN) have higher unmet dental needs, but the potential mechanisms by which parental factors can influence dental care use have not been determined. Parenting a child with SHCN can present special demands that affect parents’ well-being and, in turn, their caregiving. Hence, the study's overall aim was to apply the stress process model to examine the role of parental psychosocial factors in the association between child SHCN an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Psychosocial factors have been extensively investigated in relation to oral health and health inequalities [2][3][4][5]. Several studies have shown that the prolonged exposure to chronic psychosocial stress is associated with an increased risk of poor oral health in both children and adults [6]. Psychosocial stress has also been found to be associated with the development and progression of oral and systemic diseases and to partly explain the social inequalities in oral and general health outcomes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial factors have been extensively investigated in relation to oral health and health inequalities [2][3][4][5]. Several studies have shown that the prolonged exposure to chronic psychosocial stress is associated with an increased risk of poor oral health in both children and adults [6]. Psychosocial stress has also been found to be associated with the development and progression of oral and systemic diseases and to partly explain the social inequalities in oral and general health outcomes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“… 12 Findings linking social capital and psychological risk with poor oral health access and care in children may be even more significant in children with special care needs. 34 …”
Section: Discussionmentioning
confidence: 99%
“…For adults, we will use the Hope Home 25 screening tool which contains three questions about not seeing a dentist in the last 5 years, dental pain and/or inability to see a dentist in the last 6 months. For children, we will use the Gazzaz 26 questions on delayed or forgoing any dental visit and no preventive dental care visit in the past 12 months. A positive answer to any of the questions will be considered an unmet oral health need for the purpose of this study.…”
Section: Methods and Analysismentioning
confidence: 99%